Geopolymer as well cement and its mechanical integrity under deep down-hole stress conditions: application for carbon capture and storage wells - Nasvi, M.C.M. (Springer Science and Business Media Deutschland GmbH, 2016)
With regard to the safety, environmental impact and sustainability of carbon capture and storage (CCS) projects, the integrity of injection and production wells plays a major role. In a CCS project, mechanical integrity of well cement should be maintained to sustain the required mechanical strength throughout the life of an oil/gas and CO2 sequestration well. One of the major issues with existing Portland cement based oil well cement is cement degradation in CO2-rich environment. On the other hand, geopolymer cement possesses excellent acid resistant characteristics, shows higher mechanical strength and durability and demonstrates lower permeability. Therefore, this research work focused on studying the mechanical integrity of geopolymers under two different down-hole conditions: (1) effect of CO2 on mechanical behaviour of geopolymers and (2) hydraulic fracturing of geopolymers to study the mechanical integrity under down-hole stress conditions. To study the mechanical integrity under CO2 rich environment, geopolymers were tested in CO2 chamber at a pressure of 3Â MPa for up to 6Â months and compressive strength and microstructural testings were conducted. It was noted that strength values of geopolymers did not change significantly in CO2 environment for 6Â months. There were only about 2Â variations in compressive strength values in CO2 compared to the initial strength value. Scanning electron microscopy (SEM) test results revealed that there is no significance variation in the microstructure of geopolymer after 6Â months in CO2. For hydraulic fracturing experiment, four different tests were conducted with various injection pressure (Pin), axial stress (Ï1), confining pressure (Ï3) and tube length (30 and 40Â mm). Geopolymers could not be fractured in any of the four tests, in which maximum values of Pin of 23Â MPa and Ï1 of 59Â MPa were used. There was no fracture development in geopolymers despite maximum ratios of Pin/Ï3 of 3.8 and Ï1/Ï3 of 13.3 was tested. Tests could not be repeated with higher ratios of Pin/Ï3 and Ï1/Ï3 due to the limitation with the triaxial set-up used. Since there is no fracture development in geopolymers at higher ratios of Pin/Ï3 and Ï1/Ï3, it is concluded that required mechanical integrity can be observed when geopolymers are used as well cement. Â© 2016, Springer International Publishing Switzerland.